Kualitas Pelayanan Kredit, Kepuasan Nasabah dan Loyalitas Nasabah Studi pada PT. Bank Mandiri Tbk - Gunawan Saputra (Jurnal Wacana Ekonomi, 2020)
The purpose of this study was to determine the effect of credit service quality on customer satisfaction and its impact on customer loyalty at PT Bank Mandiri (Persero) Tbk with 140 respondents using a sampling technique called purposive sampling. This study uses Structural Equation Modeling (SEM) analysis with the help of the AMOS program. The results of this study indicate that service quality has a positive and significant effect on customer satisfaction, customer satisfaction has a positive and significant effect on customer loyalty and service quality and customer satisfaction has a positive and significant effect on customer loyalty.